2020
DOI: 10.1177/2394901520907722
|View full text |Cite
|
Sign up to set email alerts
|

Government Infrastructure Expenditure and Investment Drive in an Emerging Market Economy: Evidence from Nigeria

Abstract: Government infrastructure expenditure in an emerging market economy is critical for stimulating investment that will, in turn, foster economic growth. Given the recent growth in government infrastructure expenditure and the present deplorable state of infrastructure in Nigeria and in most emerging market economies, it becomes necessary to investigate whether the increasing government infrastructure expenditure actually drives both domestic investment and foreign direct investment (FDI). Thus, this study aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
7
1
Order By: Relevance
“…As seen in Model 5, considering the coefficients of the variables, lnRTRANSPORT has the most significant positive effect (1,8030) on lnRFDI. It has been determined that, except for the trade openness, the findings obtained in the study were found to be in parallel with the literature (Tufaner and Şirin, 2021;Khadaroo and Seetanah, 2010;Wheeler and Mody, 1992;Loree and Guisinger, 1995;Mike and Oransay, 2015;Morisset, 2001;Azolibe et al, 2020;Asiedu, 2002;Pradhan et al, 2013;Bakar et al, 2012;Rehman et al, 2011;Ahmad et al, 2015). While the trade openness ratio is expected to affect the inward FDI positively, the findings do not match the literature.…”
Section: Methodology Descriptives Empirical Results and Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…As seen in Model 5, considering the coefficients of the variables, lnRTRANSPORT has the most significant positive effect (1,8030) on lnRFDI. It has been determined that, except for the trade openness, the findings obtained in the study were found to be in parallel with the literature (Tufaner and Şirin, 2021;Khadaroo and Seetanah, 2010;Wheeler and Mody, 1992;Loree and Guisinger, 1995;Mike and Oransay, 2015;Morisset, 2001;Azolibe et al, 2020;Asiedu, 2002;Pradhan et al, 2013;Bakar et al, 2012;Rehman et al, 2011;Ahmad et al, 2015). While the trade openness ratio is expected to affect the inward FDI positively, the findings do not match the literature.…”
Section: Methodology Descriptives Empirical Results and Discussioncontrasting
confidence: 49%
“…The list of countries included in the study is given in the appendix, and since the relevant data of 8 other OECD member countries 3 could not be accessed, they could not be included in the model. In this study, besides total transportation infrastructure investment expenditures (rail, road, waterway, maritime port, airport), which is one of the explanatory variables used by the empirical literature, trade openness, inflation, and economic growth are included in the econometric model as explanatory variables (Asiedu, 2002;Khadaroo and Seetanah, 2010;Cheng and Kwan, 2000;Azolibe et al, 2020, Tufaner and Şirin, 2021, Özcan and Arı, 2010. The study's dependent variable was the ratio of foreign direct investments to GDP.…”
Section: Methodology Descriptives Empirical Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, to our knowledge, this inquiry is the first in Nigeria to explore the effects of PCE on EP. The positioning of the study also differs considerably from a strand of public expenditure literature in Nigeria which have majorly concentrated on inter alia: public expenditure and quality of life (Jeff-Anyeneh et al , 2020; Adegboyo, 2020; Jideofor et al , 2021); public expenditure and economic growth (Onifade et al , 2020; Aluthge et al , 2021) and public expenditure and investments (Usman and Abdulsamad, 2017; Azolibe et al , 2020; Azolibe, 2021). Second, unlike the only other study in this field (Nguyen and Su, 2021a), which focused on 56 developing nations and employed four energy access indicators as EP proxies, this study looks at Nigeria with additional EP indicators.…”
Section: Introductionmentioning
confidence: 96%
“…Asongu, Akpan, and Isihak (2018) have confirmed that the available natural resources and institutional quality are insignificant for FDI inflows into Brazil, Russia, India, China, and South Africa countries. Azolibe, Okonkwo, and Adigwe (2020) find that the relationship between government spending on infrastructure and FDI is insignificant. Similarly, Vijayakumar, Sridharan, and Rao (2010) concluded that the impact of trade openness and economic stability (measured by inflation rate) is insignificant on FDI.…”
Section: Introductionmentioning
confidence: 99%